2012
DOI: 10.4161/hv.20694
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus subtilis

Abstract: Most pathogens enter the body through mucosal surfaces. Mucosal immunization, a non-invasive needle-free route, often stimulates a mucosal immune response that is both effective against mucosal and systemic pathogens. The development of mucosally administered heat-stable vaccines with long shelf life would therefore significantly enhance immunization programs in developing countries by avoiding the need for a cold chain or systemic injections. Currently, recombinant vaccine carriers are being used for antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 72 publications
0
28
0
Order By: Relevance
“…First, spore-forming B. subtilis is a non-pathogenic and non-invasive aerobic Gram-positive bacterium [8, 9]. Spores of various Bacillus species are currently being used as probiotics and food supplements in both humans and animals [9, 10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, spore-forming B. subtilis is a non-pathogenic and non-invasive aerobic Gram-positive bacterium [8, 9]. Spores of various Bacillus species are currently being used as probiotics and food supplements in both humans and animals [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…First, spore-forming B. subtilis is a non-pathogenic and non-invasive aerobic Gram-positive bacterium [8, 9]. Spores of various Bacillus species are currently being used as probiotics and food supplements in both humans and animals [9, 10]. They can survive under extreme temperature, desiccation, pH and exposure to noxious chemicals and solvents [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…Based on previous studies, spores used as adjuvants were shown to increase antibody and T cell responses to a coadministered soluble antigen (Ag), including both antigen-specific CD4 ϩ and CD8 ϩ T cell responses, as well as complement-and non-complement-fixing antibody isotypes (13). Thus, we hypothesized that B. subtilis spores could function as an adjuvant for the development of a protective immune response to infection with M. tuberculosis.…”
mentioning
confidence: 99%
“…Influenza virusspecific Cytotoxic T Lymphocytes (CTLs) have been shown in animal studies to limit influenza A virus replication and to protect against lethal influenza A virus challenge [3]. In last year's a new live antigen carrier system emerged [4]. Recent studies show that recombinant endospores of Bacillus subtilis can serve as antigen carriers by fusing peptide of interest to spore coat proteins [5].…”
mentioning
confidence: 99%